2018
DOI: 10.2134/agronj2018.01.0002
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Drip Irrigation System for Water Productivity and Yield of Rice

Abstract: Core Ideas Drip irrigation improved the aerobic rice yield and water savings by 29 and 50%, respectively. The subsurface drip laid out at 0.8 m lateral distance with 1.0 L per hour dripper discharge irrigation system performed better in rice growth, physiology, and yield. Drip irrigation favored the root oxidizing power, canopy photosynthesis, and dry matter partitioning. There is a twofold increase in water productivity of aerobic rice under drip irrigation system. The use of drip irrigation in upland rice (O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
48
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(58 citation statements)
references
References 38 publications
7
48
0
3
Order By: Relevance
“…In another study, Bansal et al [95] also reported similar results in their experiments with on-farm drip irrigation in rice at Haryana, India. Parthasarathi et al [96] also reported increased aerobic rice yield and water savings by 29 and 50%, respectively at Coimbatore, India using drip irrigation. Water productivity of aerobic rice under the drip irrigation system of rice was increased by 200%.…”
Section: Drip Irrigation Under Different Rice Establishment Practicesmentioning
confidence: 98%
“…In another study, Bansal et al [95] also reported similar results in their experiments with on-farm drip irrigation in rice at Haryana, India. Parthasarathi et al [96] also reported increased aerobic rice yield and water savings by 29 and 50%, respectively at Coimbatore, India using drip irrigation. Water productivity of aerobic rice under the drip irrigation system of rice was increased by 200%.…”
Section: Drip Irrigation Under Different Rice Establishment Practicesmentioning
confidence: 98%
“…Rice ( Oryza sativa L.) is one of the most cultivated cereals and an important source of carbohydrates to two‐thirds of the global population (Parthasarathi et al ., 2018). Approximately, 75% of the produced rice is cultivated under irrigated conditions and predominantly in a flood irrigation system (Abdallah et al ., 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Lowland rice requires around 1000 to 5000 liters of water for producing one kg grain which is about twice or even more than wheat or maize water requirement [2]. However, the increasing scarcity of freshwater for agriculture and the equal demand from the nonagricultural sector threaten the sustainability of the irrigated rice ecosystem [3,4,5,6]. One of the recent developments is to grow rice as an upland crop viz.…”
Section: Introductionmentioning
confidence: 99%